Divergence and conflicts in landscape planning across spatial scales in Slovakia: An opportunity for an ecosystem services-based approach?. Issue 2 (29th November 2017) - Bezák, Peter; Mederly, Peter; Izakovičová, Zita; Špulerová, Jana; Schleyer, Christian
ABSTRACT: This paper provides a detailed analysis of environment policy implementation in national, regional and local landscape planning in Slovakia. The policy and strategic documents are assessed from the perspective of the ecosystem services (ES) concept which integrates environmental and economic objectives of the landscape planning. This paper builds on three main empirical elements: (1) review of key national policies in respect to landscape planning, (2) review of key local and regional planning, strategic and assessment documents, (3) stakeholder interviews and focus groups. Our results indicate that spatial planning and assessment processes in Slovakia based on legislation and regulations for individual sectors are mainly contradictory in some cases, rather than encompassing integrated (landscape) planning procedures. The ES concept has not been considered in any planning tools across scales. These results were found to be similar with respective EU policies, in which the limited uptake of the ES concept was also observed. Finally, the paper presents recommendations which can enhance spatial planning processes in Slovakia; using an ES-inspired integrated framework for landscape assessment and decision-making. Such improvement of planning and decision-making procedures can be exploited in real-world solutions, and provide long-term benefits for human well-being while still retaining links to ecosystem functions and processes.EDITED BY Sandra Luque